Functional group richness: implications of biodiversity for light use and lipid yield in microalgae. Issue 5 (9th July 2013) - Stockenreiter, Maria; Haupt, Florian; Graber, Anne‐Kathrin; Seppälä, Jukka; Spilling, Kristian; Tamminen, Timo; Stibor, Herwig; Buschmann, A.
<x xml:space="preserve">Abstract</x> Currently, very few studies address the relationship between diversity and biomass/lipid production in primary producer communities for biofuel production. Basic studies on the growth of microalgal communities, however, provide evidence of a positive relationship between diversity and biomass production. Recent studies have also shown that positive diversity–productivity relationships are related to an increase in the efficiency of light use by diverse microalgal communities. Here, we hypothesize that there is a relationship between diversity, light use, and microalgal lipid production in phytoplankton communities. Microalgae from all major freshwater algal groups were cultivated in treatments that differed in species richness and functional group richness. Polycultures with high functional group richness showed more efficient light use and higher algal lipid content with increasing species richness. There was a clear correlation between light use and lipid production in functionally diverse communities. Hence, a powerful and cost‐effective way to improve biofuel production might be accomplished by incorporating diversity related, resource‐use‐dynamics into algal biomass production.